Erythema multiforme: Differences between HSV‐1 and HSV‐2 and management of the disease—A case report and mini review. Issue 3 (10th February 2019) - Magri, Francesca; Chello, Camilla; Pranteda, Giulia; Pranteda, Guglielmo
Abstract: Erythema multiforme (EM) is an immune‐mediated reaction characterized by target lesions and with possible mucosal involvement. Its most frequent cause is HSV, with HSV‐1 more common than −2. It is usually self‐limited but it can show recurrences. We report a peculiar case of recurrent herpes‐associated erythema multiforme (HAEM) in a 35‐year‐old man. The patient was affected by both herpes labialis and genitalis, but the typical target lesions were only associated with recurrent herpes labialis. Here, we hypothesize about the pathogenic differences between HSV‐1 and HSV‐2, and discuss the therapeutic management of HAEM.